Broadband and Compact Circularly Polarized MIMO Antenna With Concentric Rings and Oval Slots for 5G Application - Kulkarni, Jayshri; Sim, Chow-Yen-Desmond; Gangwar, Ravi Kumar; Anguera, Jaume (IEEE access, 2022)
A broadband and compact size circularly polarized (CP) two-port multiple input multiple output (MIMO) antenna with a footprint of 25 mm ×20 mm is investigated. The designed oval-shaped MIMO antenna employs concentric rings with oval slots (CROS), along with a circular radiator and two open-ended parallel protruded stubs. The CP radiation is achieved by embedding three oval slots, in which two of them are deployed at the left and right side of the concentric rings, whereas the third one is deployed at the top section of the concentric rings. The measured 10-dB impedance bandwidth of the proposed MIMO antenna was 46.30% (3.12-5.00 GHz), and its corresponding 3-dB axial ratio bandwidth (ARBW) was 41.34% (3.30-5.02 GHz). Furthermore, very wide beamwidths of 137^{° }± 0.2 and 154^{° }± 0.2 were measured in the right-hand circular polarization (RHCP) and left-hand circular polarization (LHCP) radiation patterns, respectively. The minimum achieved isolation between the antenna elements is 18.50 dB without using any additional decoupling structure, and the calculated envelope correlation coefficient (ECC) < 0.03.